When I was young in the mountains - Rylant, Cynthia; Goode, Diane (New York : Dutton, 1982)
Reminiscences of the pleasures of life in the mountains as a child.
Keywords: Mountain life -- Juvenile fiction; United States -- Social life and customs -- 20th century -- Juvenile fiction